Commentary: the link between attachment and social competence in early childhood. Issue 3 (4th May 2019) - Waters, Harriet S.
ABSTRACT: The relationship between attachment and social competence in early childhood has been established by the broader literature, but has fallen short of providing specificity of developmental mechanisms bridging the two. This special issue proposes that secure base script knowledge built upon infant-caregiver experiences is the key link. The empirical articles provide support of this hypothesis across cultures sampled from four continents. All reproduce significant relations between children's secure base scripts and social competence, as well as other related social/cognitive variables. None of this would be possible if the authors had not developed new efficient scoring systems for assessing young children's script knowledge. They have not only provided a more sophisticated cognitive-based analysis of the relation between attachment and social competence, but new methodological tools to explore the relation in greater detail as well opening up the possibility of longitudinal studies and adapting the narrative techniques to assess peer-based scripts.